DFT study on ORR catalyzed by bimetallic Pt-skin metals over substrates of Ir, Pd and Au - Xueqiang Qi; Tingting Yang; Pingbo Li; Zidong Wei (Nano Materials Science, 2023)
Bimetallic Pt-skin catalyst is a class of near-surface alloy (NSA) that owns a high degree of control over composition. Herein, density functional theory (DFT) is used to calculate the energetics of oxygen reduction reaction (ORR) on Pt-skin over Ir, Pd and Au substrates. A Brønsted-Evans-Polanyi (BEP) relationship can be determined for the oxygen molecule dissociation. The binding energy of both atomic oxygen and hydroxyl radical is found to correlate well with the d band center of Pt-skin atoms. Their catalytic activities show the volcano relationship as the positions of each substrate in the periodic table. The effect of surface strain, band structure and charge transfer on the d band center is well studied, and it can be found that the surface strain effect plays a dominant role for all Pt-skin catalysts. Ir substrate makes the d band center of Pt-skin go far away from the Fermi level, while Au substrate makes it move towards the Fermi level. Being different from both Ir and Au, Pd substrate makes the d band center of Pt-skin comparable with the monometallic Pt.